Biorenewable blends of polyamide‐11 and polylactide. Issue 7 (19th July 2013) - Patel, Rakhi; Ruehle, David A.; Dorgan, John R.; Halley, Peter; Martin, Darren
<x xml:space="preserve">Abstract</x> Polyamide‐11(PA11) is melt blended with polylactide (PLA) using 0.00 to 0.10 wt% titanium isopropoxide catalyst to investigate potential compatibilizing reactions. Blend properties are characterized by differential scanning calorimetry (DSC), thermogravimetric analysis, dynamic mechanical thermal analysis, and tensile and impact testing. DSC shows two separate glass transition temperatures indicating only partial miscibility. Base etching to remove PLA domains followed by field emission scanning electron microscopy confirms the two phase nature of the blends. Storage and tensile moduli of the blends increase monotonically with increasing PLA content. Interchange reactions during reactive mixing were investigated by 13C‐NMR spectroscopy but the analysis shows little evidence of interchange reactions. This is true irrespective of catalyst level and mixing time over the temperature range from 185°C to 225°C. At the upper end of the temperature range investigated, significant degradation is observed. The combined results indicate that degradation reactions dominate over compatibilizing interchain transreactions. POLYM. ENG. SCI., 54:1523–1532, 2014. © 2013 Society of Plastics Engineers